2008
DOI: 10.1002/tox.20311
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the antibiotic effects of cylindrospermopsin on common gram‐positive and gram‐negative bacteria and the protozoan Naegleria lovaniensis

Abstract: The importance of the toxin cylindrospermopsin to the function and fitness of the cyanobacteria that produce it remains a matter of conjecture. Given that the structure of cylindrospermopsin has commonalities with other antibacterial protein synthesis inhibitors, such as streptomycin, authors tested the possibility that the toxin might act as an antibacterial compound that can kill competing microbes. Escherichia coli, Bacillus subtilis, Staphylococcus aureus, and Pseudomonas aeruginosa were tested by the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…In many systems, the biomass of protozoans often exceeds that of metazoans, in fact, protozoans are often the most important grazers on phytoplankton [46]. Unsurprisingly, a number of studies have demonstrated adverse effects of cyanotoxins on protozoans: For example, CYN is toxic to the amoeba Naegleria lovaniensis [47], and the protozoans Spirostomum ambiguum and Tetrahymena termophyla are both sensitive to MC [48]. Conversely, a number of protozoan grazers are known to actively feed and grow on toxic cyanobacteria [46,49].…”
Section: Exploring the Evidencementioning
confidence: 99%
“…In many systems, the biomass of protozoans often exceeds that of metazoans, in fact, protozoans are often the most important grazers on phytoplankton [46]. Unsurprisingly, a number of studies have demonstrated adverse effects of cyanotoxins on protozoans: For example, CYN is toxic to the amoeba Naegleria lovaniensis [47], and the protozoans Spirostomum ambiguum and Tetrahymena termophyla are both sensitive to MC [48]. Conversely, a number of protozoan grazers are known to actively feed and grow on toxic cyanobacteria [46,49].…”
Section: Exploring the Evidencementioning
confidence: 99%
“…Different studies have revealed the environmental toxicity of CYN towards different groups of organisms, including amphibians [11], gastropods [12], fish [13,14], plants [15], and aquatic macrophytes [16], as well as antibacterial activity [17]. CYN exposure has hepatotoxic, nephrotoxic and general cytotoxic effects and can also lead to fetal toxicity, tumor initiation, micronucleus induction and chromosome loss [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutagenic and carcinogenic effects of CYN have also been demonstrated (Humpage et al 2000; Falconer and Humpage 2001; Bazin et al 2010). Recent studies have revealed the environmental toxicity of CYN towards different groups of organisms, including amphibians (Kinnear et al 2007), gastropods (White et al 2006), fish (Gutiérrez-Praena et al 2012), plants (Metcalf et al 2004), and aquatic macrophytes (Kinnear et al 2008), as well as antibacterial activity (Rasmussen et al 2008). Two other structural variants of CYN have been isolated: deoxy-cylindrospermopsin (Norris et al 1999) and 7-epicylindrospermopsin (Banker et al 2000).…”
Section: Introductionmentioning
confidence: 99%